Attitude of Child Bearing Mothers towards House-To-House Immunization of Children against Poliomyelitis in Ebonyi North Senatorial Zone of Ebonyi State - Nkiru , Edith Obande-Ogbuinya (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
Regardless of the extensive pulse polio immunization (PPI) administered to children during house-to-house immunization strategy which was introduced by the Nigerian government, eradicating polio out of the country still remains a mirage. Nigeria as a country is not yet free from polio virus together with Afghanistan and Pakistan. The study thus investigated the attitude of child bearing mothers towards house-to-house immunization of children against poliomyelitis in Ebonyi North Senatorial Zone of Ebonyi State. There was one research question and two null hypotheses to guide the study. The population comprised 210,083 child bearing mothers in Ebonyi North Senatorial Zone. The multistage sampling technique was used to pick 100 child bearing mothers used as sample for the study. The instrument for data collection was a self structured attitude of mothers towards house-to-house immunization of children against poliomyelitis (AMTHHIOCAP) questionnaire. The reliability of the instrument was tested using Cronbach Alpha and a reliability coefficient of 0.82 was established. The result of the study revealed that attitude of the child bearing mothers towards house-to-house immunization of children against poliomyelitis in Ebonyi North Senatorial Zone of Ebonyi State was negative. There was significant difference in attitude of the childbearing mothers towards house-to-house immunization of children against poliomyelitis based on educational status. However, there was no significant difference in attitude of the mothers based on religion. By the result of the study, it was concluded that all efforts should be made to change the negative attitude towards the immunization strategy among the childbearing mothers. It was thus recommended among others that health educators should be deployed to various communities so as to sensitize and create awareness among the child bearing mothers on the need for their children to be presented during house-to-house immunization and also bring to their fore, the fatal consequences of avoiding and not immunizing their children.